ANALISIS BAGIAN KEARSIPAN PADA KANTOR WILAYAH BADAN PERTANAHAN NASIONAL PROVINSI SULAWESI TENGAH - Lestari, Widi; Hasbullah, Hasbullah; Khairil, Muhammad (Katalogis, 2019)
The purpose of this study was to determine the performance of the Archives Section at the Regional Office of the National Land Agency of Central Sulawesi Province. This research uses descriptive qualitative type, with the number of informants involved as many as 5 informants through Purposive Sampling techniques. In addition, in the data collection technique in this study through observation, interviews and documentation. With the method of analyzing data through the stage of condensation of data, presenting data, and drawing conclusions or verification.Judging from the results of the study, it was concluded that the performance of the Archives Section at the Regional Office of the National Land Agency of Central Sulawesi Province was still considered to be not maximal, this is due to the quality aspects of the Archives Department's performance at the Regional Office of the National Land Agency of Central Sulawesi Province. maksimal, this is clearly illustrated in the results of research that show that employees at the archives sometimes still not able to complete several tasks in a timely manner, and employees at the archives at the Regional Office of the National Land Agency of Central Sulawesi Province also sometimes still unable to work carefully. In addition, other causes are also caused by aspects of responsibility that are considered still not running maksimal, where the results of the study show that employee discipline is still low, this is clearly illustrated in research that shows that sometimes employees are still late to the office and sometimes employees do not use appropriate service attributes or clothing, and sometimes employees are too relaxed in dealing with the assigned work completed.